Associations and outcomes of cardiovascular calcifications by computed tomography in atrial fibrillation patients. (14th October 2021) - Wang, T K M; Chan, N; Cremer, P C; Kanj, M; Baranowski, B; Saliba, W; Wazni, O M; Jaber, W A
Abstract: Background: Coronary (CAC), mitral annular (MAC), aortic valve (AVC) and thoracic aortic (TAC) calcifications are known imaging biomarkers for cardiovascular risk in the general population. Despite this, their prognostic value are not well established in atrial fibrillation (AF) patients who have elevated risk for cardiovascular events. Purpose: We assessed the associated factors and outcomes of cardiovascular calcifications detected by computed tomography (CT) in AF patients undergoing pulmonary vein isolation (PVI). Methods: Consecutive AF patients enrolled in a prospective PVI registry during 2014–2018 with CT performed within 1-year of their procedure were reviewed for the presence of cardiovascular calcifications on CT. Risk factors and outcomes for each type of cardiovascular calcifications were analyzed in univariable and multivariable regression models. Results: Amongst 3604 AF patients, there were 2238 (62.1%), 308 (8.6%), 572 (15.9%) and 1048 (29.1%) patients with CAC, MAC, AVC and TAC respectively. Factors independently associated with these cardiovascular calcifications are listed in Table 1. During mean follow-up of 2.8±1.6 years, there were 97 (2.7%) all-cause deaths, and 158 (4.4%) major adverse cardiovascular events (MACE). Forest plots of unadjusted and adjusted hazards ratios of cardiovascular calcifications at predicting these outcomes are shown in Figure 1. Conclusion: Cardiovascular calcifications especially CAC are prevalent in AF patients, and share common risk factors with cardiovascular events, except for female being protective for CAC and AVC but having higher risk of MAC and TAC. Although all cardiovascular calcifications were associated with death and MACE in unadjusted analyses, only CAC remained so for both outcomes in adjusted analyses. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): National Heart Foundation of New Zealand